Comparison of three different surgical techniques for designing pharyngeal flaps according to findings of videonasopharyngoscopy and multiplanar videofluoroscopy. (May 2019) - Ysunza, Pablo Antonio; Chaiyasate, Kongkrit; Rontal, Matthew; Shaheen, Kenneth; Bartholomew, Blake
Abstract: Background: Velopharyngeal insufficiency (VPI) occurs when the velopharyngeal sphincter (VPS) is unable to completely seal anatomical closure between the nasal and oral cavities during speech. Palatal repair can restore VPS function but the prevalence of VPI after repair has been reported ranging from 20% to 40%. The combination of flexible videonasopharyngoscopy (FVNP) and multiplanar videofluoroscopy (MPVF) has been reported as the best approach for assessing the VPS mechanism and planning effective surgical procedures aimed to correct VPI. Objective: To study the outcome of three different techniques for performing pharyngeal flaps with the common denominator of individually designing the flap according to findings of VFNP and MPVF. Material and methods: A total of 140 cases of pharyngeal flap surgery were reviewed. Three surgeons performed 3 different surgical techniques. All cases underwent nasometry, VNP and MPVF preoperatively. All surgical procedures were carefully planned and designed according to findings of VNP and MPVF. Results: Nasal emission was completely eliminated in all cases. One-hundred-thirty-four patients (95%) demonstrated mean nasalance within normal limits after the surgical procedure whereas 6 patients persisted with mean nasalance scores above reference values postoperatively. There were no intraoperative or postoperative complications in any of the cases. No clinical data of sleep disordered breathing was detected in any of the cases after 2 months of postoperative follow-up. However, one case presented with clinical data of sleep disordered breathing 8 months postoperatively. Conclusions: The results of this study suggest that as long as pharyngeal flaps are being designed according to the findings of imaging procedures, different surgical techniques can provide similar successful outcomes with minimal complications.